Flavonoids as Natural Anti-Inflammatory Agents Targeting Nuclear Factor-Kappa B (NF kappa B) Signaling in Cardiovascular Diseases: A Mini Review - Ker Woon Choy; Dharmani Murugan; Xin-Fang Leong; Razif Abas; Aspalilah Alias; Mohd Rais Mustafa (Frontiers Media Sa, 2024)
Indexed by WOS